Risk factors during pregnancy and delivery for the development of Perthes' disease, a nationwide Swedish study of 2.1 million individuals - Maria Lindblad; Ann Josefsson; Marie Bladh; Gunilla Sydsjö; Torsten Johansson (BMC, 2020)
Abstract Background To ascertain or disprove a correlation between suboptimal birth characteristics, breech position at delivery and development of Perthes' disease. Methods Study material was collected from nationwide registers regarding diagnoses, birth statistics and delivery data. As study population were included children with a diagnosis code for Perthes' disease who were alive and living in Sweden at age 13. Children with missing birth statistics were excluded. All children with no Perthes' disease diagnosis were used as control group. Both single and multiple logistical regression analyses were used to calculate OR for the included characteristics. Results Children in breech position had a higher risk for developing Perthes' disease. Children with Perthes' disease had also a higher probability of having been born pre-term, very pre-term or post-term. Lower than normal birth weight and a lower Apgar-score were also associated with Perthes' disease. Conclusions There is a correlation between breech birth and development of Perthes' disease. There is also correlation to suboptimal birth characteristics. Despite our findings this should not be used for screening of Perthes' disease as the percentage of children who actually develop it is very low. Also, as of yet there is no possibility to diagnose Perthes' disease before the presence of skeletal changes. Our findings could be important in finding the cause of Perthes' disease and therefore developing better diagnostics, treatment and prevention.